Women Farmers Group Participation in Empowering Local Food Security - Windiasih, Rili; Sari, Lilik Kartika; Prastyanti, Shinta; Sulaiman, Adhi Iman; Sugito, Toto (CV. Inara, 2023)
Women's participation in socio-economic development at the local level is important and strategic because women have two roles as actors in developing a household by taking care of children and helping in the family economy. This study aims to the participation of farmer women's groups in empowering local food security as a Corporate Social Responsibility (CSR) program in Cilacap Regency, Central Java Province, Indonesia. This study used the Participatory Learning and Action (PLA) method to involve 20 informants from members and administrators of the Women Farmers Group (WFG) of Sumber Pathedan and 14 academics, namely lecturers and students. Data were collected through interviews, Focus Group Discussions (FGD), observation, and documentation with participatory analysis to produce natural and sustainable reality constructions. The results showed that WFG had the motivation and cohesiveness to become an entrepreneur after receiving socio-economic empowerment in the form of cultivating food security for vegetables and post-harvest processed products from the CSR program. However, it requires program sustainability such as assistance to continue to be able to harvest productively in the dry season. Then it requires the support of home production equipment and supplies to increase the productivity of postharvest products.